Recommendations for the management of indeterminate HIV PCR results within South Africa’s early infant diagnosis programme - Ahmad Haeri Mazanderani; Karl-Günter Technau; Nei-yuan Hsiao; Jean Maritz; Sergio Carmona; Gayle G. Sherman (Southern African Journal of HIV Medicine, 2016)
Indeterminate HIV PCR results represent missed diagnostic opportunities within South Africa's early infant diagnosis (EID) programme. These results not only delay diagnosis and appropriate management but are also a source of confusion and apprehension amongst clinicians and caregivers. We describe the extent of indeterminate HIV PCR results within South Africa's EID programme and provide recommendations for the management of these cases, both in terms of laboratory practice and the clinical care of the infants.